Managerial component in market-based socio-cultural activities - Щепілова, Руслана; Попова, Ніна (Інформаційні технології і системи в документознавчій сфері, 2024)
The managerial aspect of socio-cultural activities involves organizing, controlling, and stimulating cultural endeavors. In Ukraine, cultural institutions enjoy autonomy in promoting art and preserving heritage. The state supports cultural professionals and fosters international cultural exchange to meet the needs of Ukrainians worldwide.